ADDITION OF HONEY AND TIME FERMENTATION ON THE QUALITY OF RED BEAN FERMENTED MILK (Phaseolus vulgaris L.) - Rahmayuni '; Faizah Hamzah; Fifin Nofiyana (Universitas Riau, 2013)
This research is to analyse influence of addition of honey and time fermentation on the quality of red beanfermented milk. A Complete Random Design with two factors and three replications was applied in this research.The first factor was addition of honey 5%, 10% and 15% and the second factor was time fermentation of 8 hour,10 hour and 12 hour. Data were analyzed using Analysis of Varian (ANOVA) and continued by using Duncan’sNew Multiple Range Test (DNMRT) the level 5%. The result show that the addition of honey and time fermentationhad no significant interaction. Addition of honey and time fermentation significantly effects the pH and total acidtitration, but had no significant effect on the organoleptic parameters.Key words: red bean, honey, time fermentatin, milk fermentation